Barriers and facilitators to implementation research on pharmacist-led medication reviews in memory clinics: A qualitative study using the TDF-COM-B - Rishabh Sharma; Yusra Aslam; Sadaf Faisal; Carrie McAiney; Feng Chang; Cheryl A. Sadowski; Linda Lee; Manonita Roy; Bincy Baby; Muhammad Mamdani; Tejal Patel (PLoS ONE, 2026)
Background Improving medication use is important in patients with cognitive impairment and dementia. In memory clinics within primary-care settings, pharmacists perform structured medication reviews targeting medication-related problems in this population. The impact of pharmacist-led medication reviews in such clinics has not been examined previously. However, implementing research in clinical environments is fraught with challenges. Thus, this research focuses on identifying barriers and facilitators that would impact the implementation of research projects examining medication reviews in primary-care based memory clinics. Methods We conducted a qualitative study using focus group discussions with pharmacists, physicians, care partners, and other healthcare professionals. Semi-structured guides informed by the Theoretical Domains Framework (TDF) were used to facilitate discussions. Using the TDF–COM-B (Capabilities-Opportunities-Motivation-Behaviour) approach, we identified and analyzed barriers and facilitators to implementing research on pharmacist-led medication reviews and generated potential intervention strategies. Results Eighteen stakeholders across three focus groups identified several key barriers, including communication gaps, unclear interdisciplinary roles, participant burden, and limited resources across multiple TDF domains. Facilitators included the perceived impact of medication reviews (beliefs about consequences), patient involvement in research (decision processes), study procedural knowledge (knowledge), pharmacist recognition (social/professional role and identity), and standardized medication reviews (skills). Implementation strategies included providing standardized training, simplifying study procedures with digital tools and templates, involving study coordinators, and engaging patients and care partners in decision-making. Barriers such as communication gaps, unclear interdisciplinary roles, participant burden, and resource constraints were addressed through workflow redesign, financial incentives, and fostering collaboration and institutional support. Conclusion This study identified key barriers and facilitators to implementing research on pharmacist-led medication reviews in memory clinics, highlighting several areas with direct policy relevance. These findings point to important policy needs, including clearer interdisciplinary roles, improved communication, adequate resource support, and standardized training to enhance the feasibility and sustainability of pharmacist-led medication review interventions, ultimately supporting successful research implementation and improving medication use in older adults with cognitive impairment and dementia.